Dissolved 129 Xe lung MRI with four‐echo 3D radial spectroscopic imaging: Quantification of regional gas transfer in idiopathic pulmonary fibrosis - Collier, Guilhem J.; Eaden, James A.; Hughes, Paul J. C.; Bianchi, Stephen M.; Stewart, Neil J.; Weatherley, Nicholas D.; Norquay, Graham; Schulte, Rolf F.; Wild, Jim M. (Magnetic resonance in medicine, 2021)
Imaging of the different resonances of dissolved hyperpolarized xenon-129 ( Xe) in the lung is performed using a four-echo flyback 3D radial spectroscopic imaging technique and is evaluated in healthy volunteers (HV) and subjects with idiopathic pulmonary fibrosis (IPF). 10 HV and 25 subjects with IPF underwent dissolved Xe MRI at 1.5T. IPF subjects underwent same day pulmonary function tests to measure forced vital capacity and the diffusion capacity of the lung for carbon monoxide (DL ). A four-point echo time technique with k-space chemical-shift modeling of gas, dissolved Xe in lung tissue/plasma (TP) and red blood cells (RBC) combined with a 3D radial trajectory was implemented within a 14-s breath-hold. Results show an excellent chemical shift separation of the dissolved Xe compartments and gas contamination removal, confirmed by a strong agreement between average imaging and global spectroscopy RBC/TP ratio measurements. Subjects with IPF exhibited reduced imaging gas transfer when compared to HV. A significant increase of the amplitude of RBC signal cardiogenic oscillation was also observed. In IPF subjects, DL % predicted was significantly correlated with RBC/TP and RBC/GAS ratios and the correlations were stronger in the inferior and periphery sections of the lungs. Lung MRI of dissolved Xe was performed with a four-echo spectroscopic imaging method. Subjects with IPF demonstrated reduced xenon imaging gas transfer and increased cardiogenic modulation of dissolved xenon signal in the RBCs when compared to HV.